A review of piling industry practices in Dubai, UAE: proposed UCS-based correlations. Issue 2 (30th August 2018) - Latapie, Benoît; Albelda, Rhea A; Abou Samra, Michelle; Alzaylaie, Marwan; Sumputh, Joyshwin
Abstract : There is limited published information available on design guidance and performance of deep pile foundations in Dubai, UAE. In response to this situation, the piling industry tends to be over-conservative when designing foundation systems for buildings and infrastructure. Consultants, pile testing experts and the Dubai Creative Clusters Authority decided to collaborate with a common goal: share information with the industry and make pile design recommendations to help colleagues prevent the large-scale over-engineering of pile foundations currently ongoing in the Emirate of Dubai. A total of over 200 pile load test results, from which 91 are preliminary pile load tests, were available to the authors to conduct the study presented in this paper. The interpretation of the available information combined with finite-element back-analyses enabled the authors to propose Dubai-specific relationships between the rock's unconfined compressive strength and the pile's ultimate skin friction resistance. Relationships between the rock's unconfined compressive strength and its elastic modulus are also proposed.